The Research on the Influence of Ethical Value on the Formation and Exertion of Human Capital: Based on the Perspective of Protestant Work Ethic - PAN Yixing, YUAN Jing, (Journal of Research for Christianity in China (JRCC), 2025)
In the face of the economy into the “new normal” phase, China can use the young labor force every year on the decline. To continue to maintain the stable development of China's economy, the improvement of human capital is particularly important in the case of the decline of labor population size. This paper discusses the formation and development of human capital through the protestant work ethics. It is found that four kinds of human capital in the protestant work ethics: stimulating the positive attitude of people in the enterprise, promoting the employee restraint and thrift, cultivating the entrepreneurial spirit and the popularization of entrepreneurs , promoting education and stimulating the enthusiasm of people to learn the professional technology. The research results of this paper can be used to enhance the human capital of the existing enterprise employees from the perspective of ethical value.
Keywords: Ethic Value; Human Capital; Protestant Work Ethic